2015
DOI: 10.1159/000381752
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Value of Different Systematic Prostate Biopsy Methods in the Detection of Prostate Cancer with Ultrasonographic Hypoechoic Lesions - A Comparative Study

Abstract: Objective: To assess if a less extended biopsy in the transperineal approach is sufficient for detection of prostate cancer (PC) in patients with hypoechoic lesions. Methods: This was a prospective study of 167 consecutive patients with prostate hypoechoic lesion and who underwent transperineal ultrasound (TPUS)-guided 12-core and hypoechoic lesion core biopsy between January 2012 and February 2013. Results: PC was detected in 64.1% (107/167) of patients. The PC detection rate of the 12-core prostate biopsy sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
0
2
1
Order By: Relevance
“…In our study, 68.53% of the patients with hypoechoic lesions were diagnosed as PCa by 10-core TP-PBx. The detection rate was a little higher than the recent reports with the detection rate of about 62.9%–67.2% by the same biopsy method [ 28 , 29 ]. The reasons may attribute to our larger population and different skills of urologists in different medical centers.…”
Section: Discussioncontrasting
confidence: 63%
“…In our study, 68.53% of the patients with hypoechoic lesions were diagnosed as PCa by 10-core TP-PBx. The detection rate was a little higher than the recent reports with the detection rate of about 62.9%–67.2% by the same biopsy method [ 28 , 29 ]. The reasons may attribute to our larger population and different skills of urologists in different medical centers.…”
Section: Discussioncontrasting
confidence: 63%
“…19 Some reports suggest that a limited sextant biopsy (six cores) could also be sufficient provided that the hypoechoic areas if present, are adequately sampled. 20 However, there is now a clear consensus that a sextant biopsy is insufficient; a 10or 12-core biopsy should be routinely employed including the targeting of suspicious lesions on TRUS. 21 We performed a systematic 12-core prostate biopsy including a core from suspicious hypoechoic lesion.…”
Section: Discussionmentioning
confidence: 99%
“…In theory, increasing the number of biopsy sites, especially the number of peripheral biopsy sites, can increase the detection rate of PCa, while also increasing the incidence rates of patient discomfort and complications. Xu et al compared the positive detection rates and complications of the 6‐, 10‐, 12‐, and 14‐core biopsy methods and concluded that the 10‐core method was the most suitable method for prostate biopsy, and further increasing the number of biopsy cores did not significantly improve the positive detection rate. Research has shown that complications can be substantially increased when the number of biopsy cores exceeds 12 .…”
Section: Discussionmentioning
confidence: 99%